CAPITAL POTENTIAL AND ENTREPRENEURIAL POTENTIAL AFFECTING SUSTAINABILITY OF SOCIAL ENTERPRISES BASED ON CULTURAL CAPITAL - KRUTPUKSEE, Autthawut; JANSURI, Athip; LALAENG, Chanyaphak (Asian Administration and Management Review, 2024)
This research aimed to study causal variables, capital potential and entrepreneurial potential affecting sustainability of social enterprises based on cultural capital. The study was conducted among members of social enterprises in community social enterprise development model project supported by Art & Culture for Health Literacy, Thai Health Promotion Foundation (THPF) in cooperation with network partners in 4 regions consisting of the project on products from wisdom to wards Mon Pin Community Enterprise, Chiang Mai province, Sawathi Muang Samdee Sustainable Community Enterprise project, Khon Kaen province, Community Social Enterprise Pilot Project in Banglampu, Bangkok and “Songkhla Heritage” Community Enterprise Model Development Project , Songkhla province. The multiple regression analysis results of capital potential showed that cultural capital, human capital, and social capital had statistically significant effects on sustainability of social enterprises. Capital potential was effective to collaboratively predict and describe sustainability of social enterprises by 38.9%. The multiple regression analysis results of entrepreneurial potential indicated that entrepreneurial potential with respect to achievement competencies, planning competencies, and power competencies had statistically significant effects on sustainability of social enterprises. Capital potential was effective to collaboratively predict and describe sustainability of social enterprises by 62.9%.